BENTUK WACANA MEDIA MASA PRANCIS TENTANG PERISTIWA DI INDONESIA - Wulan Tri Astuti (University of Muhammadiyah Purwokerto, 2008)
A discourse always has a topic which is included in a proposition. Topic is also about the theme that is being discussed in a discourse or in main idea. This research analyzes the structure of French o line media discourse and communication analysis, with the macro structure, micro structure, and super structure approach. The result shows that based on the macro structure approach, media discourse is divided into 5 element; which are the title, date, source, number of word , and text resume. Macro structure also refers to the theme, topic or main idea of the rubric discourse. Topic unity can be achieved by several ways; referring, ellipsis, pronominalize, repetition, and lexical equivalency. According to the micro structure approach, there are parts of text, such as: word, sentence, phrase, proposition, and image. Micro structure is related with the relation between proposition. The relation that is found from the data is argumentative relation and topicalisation relation; while according to the super structure approach, the discourse is related to the framework and part that is being arranged in the text as a whole.